2020
DOI: 10.18553/jmcp.2020.26.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Projecting the Long-Term Economic Impact of Once-Monthly Paliperidone Palmitate Versus Oral Atypical Antipsychotics in Medicaid Patients with Schizophrenia

Abstract: BACKGROUND: Recent evidence has demonstrated that, over 12 months, pharmacy costs associated with switching nonadherent recently relapsed patients from oral atypical antipsychotics (OAAs) to once-monthly paliperidone palmitate (PP1M) were offset by reduced relapse rates and schizophrenia-related health care costs. In addition, earlier use of PP1M may generate greater cost savings. OBJECTIVE: To project the long-term economic impact when a proportion of nonadherent patients with a recent relapse switch from OAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 27 Furthermore, a subanalysis from the present study, conducted in patients with at least 1 prior hospitalization, reported that switching from oral RIS/PALI to PP1M may significantly improve HRU and provide potential cost savings in VHA database members with schizophrenia. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 27 Furthermore, a subanalysis from the present study, conducted in patients with at least 1 prior hospitalization, reported that switching from oral RIS/PALI to PP1M may significantly improve HRU and provide potential cost savings in VHA database members with schizophrenia. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Good medication adherence is the key to the effectiveness of drug treatment. Poor medication adherence will cause many problems in schizophrenic patients 9 , 10 . First, low medication compliance will lead to low efficacy and high relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Positive symptoms refer to a change in behaviour or thoughts characterised by hallucinations and delusions while negative symptoms represent diminution in emotions, thinking and movement (Van Os & Kapur, 2009). Effective therapies and treatments for managing schizophrenia aim to reduce relapse of these symptoms (El Khoury et al, 2020). Adherence to antipsychotic medication has become a crucial part of care in reducing experiences and symptoms of mental illness in Australia and internationally (Prerna & Ivan, 2020).…”
Section: Introductionmentioning
confidence: 99%